The Effect of Tourism Development on Labor Absorption in Central Java (Efficient: Indonesian Journal of Development Economics, 2023)
Tourism is one of the leading sectors in Indonesia, so the government develops this sector in a sustainable. Tourism development has a positive impact such as labor absorption. This study aims to determine the effect of the number of tourist attractions, tourists, hotels, and restaurants on employment and to see the differences touriin sm indicators in DPP Borobudur-Dieng and Semarang-Karimunjawa. The data processing method uses panel data regression analysis and different tests with panel data types during 2017 – 2020 period and analysis tools using Eviews-9 and SPSS. The results show that the variable number of tourist attractions, hotels, and restaurants has a positive and significant effect on labor absorption and the number of tourists has a positive and insignificant effect on labor absorption. Based on the results of the Differential t-test, shows that there is no significant difference in the variable number of tourist attractions, tourists, hotels, and restaurants, but the variable number of workers shows a significant difference in DPP Borobudur-Dieng and Semarang-Karimunjawa. This study suggests that the government should develop tourism by promoting tourism, improving service quality, and increasing the capacity of the tourism workforce and for the community to maintain and preserve tourism infrastructure.